Altered distribution of Ghrelin protein in mice molar development. (May 2016) - Liu, Bo; Han, Xiuchun; Feng, Wei; Cui, Jian; Hasegawa, Tomoka; Amizuka, Norio; Xu, Xin; Li, Minqi
Highlights: Ghrelin is expressed in mice molar tooth germs in all developmental stages. Ghrelin is predominately expressed in enamel organ before bell stage. Ghrelin is persistently located in ameloblasts and odontoblasts since bell stage. Ghrelin is also detected in Hertwig's epithelial root sheat. Abstract: Objective: Ghrelin, an appetite-stimulating hormone, plays diverse regulatory functions in cell growth, proliferation, differentiation and apoptosis during mammalian development. There is limited information currently available regarding Ghrelin expression during mammalian tooth development, thus we aimed to establish the spatiotemporal expression of Ghrelin during murine molar odontogenesis. Design: Immunohistochemistry was performed to detect the expression pattern of Ghrelin in mandible molar from E15.5 to PN7 during murine tooth development. Results: The results showed that Ghrelin initially expressed in the inner enamel epithelium and the adjacent mesenchymal cells below, further with persistent expression in the ameloblasts and odontoblasts throughout the following developmental stages. In addition, Ghrelin was also present in Hertwig's epithelial root sheath at the beginning of tooth root formation. Conclusions: These results suggest that Ghrelin was present in tooth organs throughout the stages of tooth development, especially in ameloblasts and odontoblasts with little spatiotemporal expression differences. However, the potential regulatory roles of this hormone in tooth development still need to be validated by functional studies.